STUDY ON DURABILITY OF TUNGSTEN CARBIDE CUTTER HEADS - Gochev, Zhivko; Vitchev, Pavlin; Vukov, Georgi (Innovation in Woodworking Industry and Engineering design, 2022)
Studies on the durability of tungsten carbide (TC) grooving and rebate cutter head and assessment of the quality of its sharpening have been conducted. The linear wear of the blade and the blunting radius when processing of massive coniferous wood and chipboard were studied. Recommendations were made regarding the preliminary preparation of the cutter heads and their effective operation.